Stem Cell-Derived Exosomes and Nanovesicles: Promotion of Cell Proliferation, Migration, and Anti-Senescence for Treatment of Wound Damage and Skin Ageing - Hyeonjin Cha; Seyoung Hong; Ju Hyun Park; Hee Ho Park (Pharmaceutics, 2020)
Extracellular vesicles (EVs), such as exosomes, are nano-sized vesicles derived from endocytic membranes and contain biomolecules such as proteins, lipids, RNAs, and DNAs for the transfer of signals to recipient cells, playing significant roles in cell-to-cell communication. Discovery of exosomes has attracted attention for possible use as next generation therapies in clinical applications; however, several studies suggest that cells secrete exosomes that perform as mediators in the tumor niche and play several roles in tumorigenesis, angiogenesis, and metastasis. Recently, stem cell-derived exosomes have been suggested as a desirable source for regenerative medicine due to their roles in the promotion of angiogenesis via migratory and proliferative mechanisms. This review is aimed at demonstrating the present knowledge of stem cell-derived exosomes and cell-engineered nanovesicles (CNVs) as proliferative, migratory, and anti-senescent therapeutic biomaterial for use in tissue regeneration; wound healing and anti-ageing are explained. We conclude this review by discussing the future perspectives of stem cell-derived exosomes and CNVs as a platform in therapeutic strategies for treatment of wound damage and skin aging.